The enlucted and their memories:: an analysis of family reports on the Trujillian Dictatorship in the Dominican Republic - Santos , Alexandre Firmo dos (2025)
The book under review is entitled Dictaduras: 14 family stories (2022), which was authored by Venezuelan Rosa Aura Ildefonso Álvarez in which she decided to gather a set of interviews in which they portray the memory and pain of mourning of the many family members who lost their loved ones as a result of the fierce persecution of the Trujillista government. This dictatorial government in the Dominican Republic was marked by violence, especially against those who opposed it. With this work, Rosa Ildefonso exposes the consequences of a dictatorial regime and its villainies in order to make younger people aware of the horrors of this traumatic event.